2011
DOI: 10.1038/leu.2011.135
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of highly differentiated CD8+ T-cells or NK-cells in patients treated with dasatinib is associated with cytomegalovirus reactivation

Abstract: The tyrosine kinase inhibitor dasatinib exerts immunosuppressive effects on T-cells and NK-cells in vitro. However, in some dasatinib-treated leukemia patients, clonal lymphocytosis with large granular lymphocyte (LGL) morphology develops, and this is associated with enhanced therapeutic responses. To elucidate the mechanistic basis for this paradoxical observation, we conducted detailed phenotypic and functional analyses of T-cell and NK-cell populations from 25 dasatinib-treated leukemia patients. All tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
76
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 51 publications
4
76
0
2
Order By: Relevance
“…Many studies have reported the immune-related adverse effects of dasatinib (7,(27)(28)(29)(30)(31)(32)(33). However, these side effects do probably not account for all the observed deleterious effects of the treatment in human patients, for example, pleural effusions and bleeding diathesis.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported the immune-related adverse effects of dasatinib (7,(27)(28)(29)(30)(31)(32)(33). However, these side effects do probably not account for all the observed deleterious effects of the treatment in human patients, for example, pleural effusions and bleeding diathesis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is conceivable that once the suppressive effect on T cells wears off, secreted IL-12 may be the driving factor. Bacterial infection or viral reactivation such as cytomegalovirus, which has been reported to be associated with dasatinibinduced hyperleukocytosis, 6 would qualify as the inflammatory trigger. In concert with the described inhibition of regulatory T cells by dasatinib, as reported in vitro 41 and in vivo, 42 these mechanisms may lead to unrestricted CD8 proliferation in the clinical setting, along with a better clinical response against the underlying leukemic disease.…”
Section: Discussionmentioning
confidence: 99%
“…4 Hyperproliferative T-cell and natural killer (NK)-cell responses are seen frequently and are associated with severe adverse effects such as colitis, pleuritis, and pulmonary hypertension. [5][6][7] However, the occurrence of such hyperinflammatory effects is associated with a better prognosis regarding the underlying leukemia. 8 Somewhat paradoxically, the patients may experience severe functional impairment of their T cells 9 because of blockade of T-cell receptor (TCR) triggering via inhibition of Lck.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 The limited in vitro data available with second-generation TKIs nilotinib (Novartis) and dasatinib (BristolMyers Squibb) show impaired antigen-specific T-cell responses [10][11][12][13][14][15] ; however, recent studies report rapid mobilization and expansion of BCR-ABL-negative lymphoid cells in dasatinib-treated patients. [16][17][18] Few studies have examined the impact of TKIs on B-cell responses to antigen in vivo, 19 although hypogammaglobulinemia has been reported in CML patients treated with imatinib. 20 A recent murine study reported that imatinib may directly impair class-switch recombination following B-cell activation through downregulation of activationinduced cytidine deaminase.…”
Section: Introductionmentioning
confidence: 99%